I assume by X2 you mean x squared (x^2)?
If so, write as ax^2+bx+c=0:
x^2 +11x +24 =0
in this case, a=1 because x^2 is not multiplied by a constant, b=11 and c=24.
To find the two solutions, use the formula:
x= (-b +�ã4ac)/(2a)
x= (-b -�ã4ac)/(2a)
X2+11x=-24
3 answers
Amendment: The square root sign was not properly processed by this website, it is supposed to say -b+ square root of 4ac for the first solution and -b- square root of 4ac for the second
Second amendment:
I see more got lost in formatting - this is what you get for using foreign version of Windows, apparently.
x= (-b +- sqrt(b^2 -4ac))/(2a)
Let us hope this works now. Sorry about the mess :-)
I see more got lost in formatting - this is what you get for using foreign version of Windows, apparently.
x= (-b +- sqrt(b^2 -4ac))/(2a)
Let us hope this works now. Sorry about the mess :-)